Alternative pathways in Angiostrongylus cantonensis (Metastrongyloidea: Angiostrongylidae) transmission. Issue 2 (28th February 2021) - Modrý, David; Fecková, Barbora; Putnová, Barbora; Manalo, Sheina Macy; Otranto, Domenico
Abstract: In order to elucidate the infection pathways of third stage larvae (L3) of Angiostrongylus cantonensis, we performed experiments to assess: (i) the shedding of L3 from two species of experimental veronicellid slugs drowned in water and the ratio of emerged larvae, (ii) the transmission of viable L3 from drowned terrestrial gastropods to aquatic snails, and (iii) the transmission of viable L3 between terrestrial snails. Molluscs were experimentally infected by first stage larvae (L1) of A. cantonensis . Significantly more L3 larvae were released from Veronicella cubensis than from Veronicella sloanei. Numerous L3 were observed in the muscular foot, and also in the connective tissue between internal organs. Experimental exposure of P. maculata to L3 of A. cantonensis liberated from other gastropod species led to their infection and the infectivity of larvae after intermediesis was demonstrated by infection of laboratory rats ( Rattus norvegicus ). The transmission of L3 was observed in three out of four experiment replications and L3 were retrieved from 6 out of 24 Subulina octona snails. The infected synanthropic molluscs represent a key component in the epidemiology of human infections by A. cantonensis . Escape of L3 larvae from bodies of dead snails or slugs and their ability to infect further gastropod hosts (intermediesis) represents a public health risk. Thus, control of molluscs living in peri-domestic environment is an essential part of prevention of human infections.